Prospects for of Processing Car Tires; Applied Mechanics and Materials; Vol. 682 : Innovation Technology and Economics in Engineering - Valuev D. V. Denis Viktorovich; Semenok A. A.; Kotova D. O.; Valueva A. V. Anna Vladimirovna (Material Science, Machining Technologies and Equipments in Mechanical Engineering, 2014)
Title screen